2021
DOI: 10.1002/cpe.6702
|View full text |Cite
|
Sign up to set email alerts
|

A review on security requirements specification by formal methods

Abstract: Security is an afterthought process for the development of software in earlier days but now the time has been changed. Now, security is on top priority and involved from the beginning of software development. Security requirements are the prime concern for the development and quality of any software product. The specification and verification of security requirements need a lot of attention from the computer science community in the process of the software development life cycle. Formal Methods are a widely us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Formal methods are rigorous, mathematically-based approaches that have demonstrated their ability to verify systems across critical properties such as reliability, safety, security, more generally, dependability and performance [9]. A full overview of formal methods for system analysis is outside the scope of the current work (for recent systematic reviews see [2], [17]) but our interest is in how formal methods, specifically the use of modelling, can be used to gain insight from systems involving humans.…”
Section: B Formal Methods For Human Experiencesmentioning
confidence: 99%
“…Formal methods are rigorous, mathematically-based approaches that have demonstrated their ability to verify systems across critical properties such as reliability, safety, security, more generally, dependability and performance [9]. A full overview of formal methods for system analysis is outside the scope of the current work (for recent systematic reviews see [2], [17]) but our interest is in how formal methods, specifically the use of modelling, can be used to gain insight from systems involving humans.…”
Section: B Formal Methods For Human Experiencesmentioning
confidence: 99%
“…It considers 38 high-quality studies from a period of 15 years and the findings include a clear predominance of the use of manual proof methods, Dolev-Yao-like attack models, and the AVISPA tool [197]. Furthermore, the work by Mishra and Mustafa [198] is claimed to be the first SLR on FM focusing on the security requirement specification. It considers 88 studies from the last 20 years and it is observed that model checking is preferred over theorem proving, while it remains a research challenge to effectively use FM in a cost-effective and time-saving way.…”
mentioning
confidence: 99%